2016
DOI: 10.1016/j.eurpsy.2016.05.003
|View full text |Cite
|
Sign up to set email alerts
|

The suicidality continuum in a large sample of obsessive–compulsive disorder (OCD) patients

Abstract: Suicidality could be analyzed as a severity continuum and patients should be carefully monitored since they present with suicidal ideation. Lower QoL scores, higher scores on the sexual dimension and a family history of suicide attempts should be considered as risk factors for suicidality among OCD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
48
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 49 publications
5
48
2
Order By: Relevance
“…Four main findings emerged. First, confirming previous studies conducted in clinical and community settings [1][2][3][4][5][43][44][45][46], individuals with OCD were at significantly increased risk of suicide attempts and death by suicide compared to individuals without OCD, and the risks were more pronounced for female than male OCD sufferers, similar to the results of another Swedish study on OCD and suicide [2]. This was anticipated in relation to suicide attempts, as nonfatal suicidal behavior is known to be more common in females [28,47].…”
Section: Discussionsupporting
confidence: 84%
“…Four main findings emerged. First, confirming previous studies conducted in clinical and community settings [1][2][3][4][5][43][44][45][46], individuals with OCD were at significantly increased risk of suicide attempts and death by suicide compared to individuals without OCD, and the risks were more pronounced for female than male OCD sufferers, similar to the results of another Swedish study on OCD and suicide [2]. This was anticipated in relation to suicide attempts, as nonfatal suicidal behavior is known to be more common in females [28,47].…”
Section: Discussionsupporting
confidence: 84%
“…Even though it did not remain significant in the regression analysis, the finding that suicide attempts rates among OCD + ADHD patients in this sample were almost two times higher compared with OCD adult subjects without ADHD is alarming. Previous studies have demonstrated that suicidality rates among OCD patients are high (Angelakis, Gooding, Tarrier & Panagioti, ; de la Cruz et al, ; Torres et al, ; Velloso et al, ) and that having suicide ideation almost doubled the risk for a suicide attempt (de la Cruz et al, ; Velloso et al, ). ADHD itself is also associated with higher mortality rates (Dalsgaard, Østergaard, Leckman, Mortensen & Pedersen, ).…”
Section: Discussionmentioning
confidence: 99%
“…BAI & BDI-II: Both BAI and BDI-II consist of 21 items, which are rated on a Likert scale ranging from 0 to 3, resulting in raw scores ranging from 0 to 63, and are indicative for the presence of anxiety or depression. The BAI is well suited to monitor anxiety treatment outcomes [49], and the obtained anxiety state is correlated with OCD symptoms [50,51]. Similarly, the BDI-II scores are associated with OCD symptoms [51] in line with the fact that around one-third of OCD patients suffer from comorbid depression [52].…”
Section: Y-bocsmentioning
confidence: 99%
“…The BAI is well suited to monitor anxiety treatment outcomes [49], and the obtained anxiety state is correlated with OCD symptoms [50,51]. Similarly, the BDI-II scores are associated with OCD symptoms [51] in line with the fact that around one-third of OCD patients suffer from comorbid depression [52]. Both measures have adequate psychometric properties [53,54].…”
Section: Y-bocsmentioning
confidence: 99%